2005
DOI: 10.1007/s11664-005-0254-7
|View full text |Cite
|
Sign up to set email alerts
|

Roughness and texture correlation of Al films

Abstract: Titanium films prepared by standard direct-current (DC) magnetron physical vapor deposition (PVD) and ionized metal plasma PVD (I-PVD), with Al (0.5wt.%Cu) films on them, were studied. The surface roughness, reflectivity, and crystalline texture of Ti on SiO 2 /Si and Al on TiN/Ti/SiO 2 /Si were investigated with the same thickness of Al, TiN, and Ti. The surface roughness of Al films with Ti/TiN underlayers was found to be capable of monitoring Al (111) texture. So, the reflectivity of Al/TiN/Ti film stack ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It was found that the MTTF of Al interconnects depends on the size and crystallographic orientation of the Al grains, where the (111) orientation gives the best results. 1,2 Therefore, a great deal of effort has been directed to obtain strongly (111) fibertextured Al films [3][4][5] ; for instance, Murray and Rodbell 6 studied the impact of oxide underlayers on the crystalline orientation of bare AlCu layers.…”
mentioning
confidence: 99%
“…It was found that the MTTF of Al interconnects depends on the size and crystallographic orientation of the Al grains, where the (111) orientation gives the best results. 1,2 Therefore, a great deal of effort has been directed to obtain strongly (111) fibertextured Al films [3][4][5] ; for instance, Murray and Rodbell 6 studied the impact of oxide underlayers on the crystalline orientation of bare AlCu layers.…”
mentioning
confidence: 99%